Dengue diagnostic test for point of care testing: a preliminary study among primary care physicians in Malaysia - Thuraiapprah, D. M.; Tin, Myo Han; Osman, Iskandar Firzada; Md Aris, Mohd Aznan; Abdullah, Fa’iza (Academy of Family Physicians of Malaysia, 2015)

(untitled)
W.H.O recommends using laboratory tests in dengue diagnosis for prevention, clinical management and control activities. Evidences regarding which dengue diagnostic tests used by primary care physicians as point of care testing (POCT) have been limited.This study was done to explore dengue diagnostic tests used by primary care physicians (PCPs) for point of care testing.